2006
DOI: 10.1097/01.mlg.0000200791.77819.eb
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear Protection by Local Insulin-Like Growth Factor-1 Application Using Biodegradable Hydrogel

Abstract: These findings demonstrate that local IGF-1 application through the biodegradable hydrogel has the potential for protection of cochleae from noise trauma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(72 citation statements)
references
References 17 publications
1
71
0
Order By: Relevance
“…It is also a recognized neuroprotective agent [9]. IGF-I passes through the blood-brain barrier [4], and studies have shown that brain injury may be prevented by systemic administration of human IGF [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also a recognized neuroprotective agent [9]. IGF-I passes through the blood-brain barrier [4], and studies have shown that brain injury may be prevented by systemic administration of human IGF [9].…”
Section: Discussionmentioning
confidence: 99%
“…However, the various studies did not diVerentiate between hearing loss of conductive, cochlear and retrocochlear origin. In studies of animal model protective drugs, local treatment with recombinant human -I (rhIGF-I) led to signiWcant protection from noise trauma [9]. Possible explanations for the eVect of IGF-I on hearing include rescue of hair cells from apoptosis and inhibition of apoptosis by downregulation of pro-apoptotic gene expression [10].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that insulin-like growth factor (IGF)-1 suppresses the apoptosis of nerve cells. Controlled release of IGF-1 from the gelatin hydrogel inhibited the ageing of acoustic nerve, resulting in suppressed deterioration of hearing hardness (Iwai et al 2006). This IGF-1 treatment has been started clinically to demonstrate good therapeutic efficacy (table 2).…”
Section: Clinical Aspects Of Tissue Engineering-based Tissue Regeneramentioning
confidence: 99%
“…After 1 week, animals implanted with BDNF-containing collagen hydrogels had significantly lower (improved) electrically-evoked auditory brainstem response thresholds, significantly higher density of surviving SGNs, and perilymph levels of BDNF over 100 times higher than control animals treated with saline Ito et al, 2005). Both collagen-glutaraldehyde hydrogels and gelatin hydrogels have been used to deliver recombinant human IGF-1 to the inner ear to prevent noise-induced damage (Iwai et al, 2006;Lee et al, 2007). Animals with these gels had lower auditory brainstem response thresholds and higher SGN survival than animals that received control gels.…”
Section: Hydrogelsmentioning
confidence: 96%